Two phospholipid scramblase 1–related proteins (PLSCR1like-a & -b) from Liza haematocheila: Molecular and transcriptional features and expression analysis after immune stimulation. Issue 87 (April 2019) - Sandamalika, W.M. Gayashani; Priyathilaka, Thanthrige Thiunuwan; Nam, Bo-Hye; Lee, Jehee
Abstract: Phospholipid scramblases (PLSCRs) are a family of transmembrane proteins known to be responsible for Ca 2+ -mediated bidirectional phospholipid translocation in the plasma membrane. Apart from the scrambling activity of PLSCRs, recent studies revealed their diverse other roles, including antiviral defense, tumorigenesis, protein–DNA interactions, apoptosis regulation, and cell activation. Nonetheless, the biological and transcriptional functions of PLSCRs in fish have not been discovered to date. Therefore, in this study, two new members related to the PLSCR1 family were identified in the red lip mullet ( Liza haematocheila ) as MuPLSCR1like-a and MuPLSCR1like-b, and their characteristics were studied at molecular and transcriptional levels. Sequence analysis revealed that MuPLSCR1like-a and MuPLSCR1like-b are composed of 245 and 228 amino acid residues (aa) with the predicted molecular weights of 27.82 and 25.74 kDa, respectively. A constructed phylogenetic tree showed that MuPLSCR1like-a and MuPLSCR1like-b are clustered together with other known PLSCR1 and -2 orthologues, thus pointing to the relatedness to both PLSCR1 and PLSCR2 families. Two-dimensional (2D) and 3D graphical representations illustrated the well-known 12-stranded β-barrel structure of MuPLSCR1like-a and MuPLSCR1like-b with transmembrane orientation toward the phospholipid bilayer. In analysis of tissue-specific expression, the highest expression of MuPLSCR1like-a was observed in the intestine, whereas MuPLSCR1like-b was highly expressed in the brain, indicating isoform specificity. Of note, we found that the transcription of MuPLSCR1like-a and MuPLSCR1like-b was significantly upregulated when the fish were stimulated with poly(I:C), suggesting that such immune responses target viral infections. Overall, this study provides the first experimental insight into the characteristics and immune-system relevance of PLSCR1 -related genes in red lip mullets. Highlights: MuPLSCR1like-a and MuPLSCR1like-b were identified from red lip mullet. Highest expression of MuPLSCR1like-a was observed in intestine. MuPLSCR1like-b was highly expressed in brain. Both genes were significantly upregulated after stimulated with poly(I:C).